The role of risks, collaboration and performance in the supply chain of manufacturing firms of Malaysia - Shahbaz, Muhammad Saeed (2019)
Malaysian manufacturing is contributing around 80 percent in the exports and consider the highest sector for employability but its growth is decreasing for a few years. After plentiful literature, it has been found that various supply chain issues not only disrupt core organization but a whole network and ultimately the economy. Previous studies show that there are limited studies available for supply chain risks. Likewise, the effects of supply chain risks on supply chain performance for Malaysian manufacturers are scarce, primarily, only few studies exists that covers overall risks. Meanwhile, there are ample strategies to deal with risks but collaboration needs to verify as a mitigation approach for all kind of risks. Thus, the aim of this study is to identify the potential supply chain risks, assess their effects of performance and verify the role of supply chain collaboration as a risk mitigation approach. To cover all three aspects of supply chain (internal to organizational, external to organizational but internal to supply chain and external to supply chain), seven risk sources were identified namely supply side risks, process side risks, demand side risks, logistic side risks, collaboration side risks, financial side risks and environment side risks. To assess the effects of these risks on performance a questionnaire was developed through a systematic process. The population of this study is 2300 manufacturing organizations listed in the Federation of Manufacturing Malaysia. The questionnaires were sent to every 5th organization by systemetic sampling. So, total 480 questionnaires were sent but received 354 responses. Data was analyzed through structural equation modeling using smart PLS. The findings revealed that all types of risks have a negative impact on supply chain performance but only supply, demand, logistic and environment side risks have a significant negative impact. Although, logistic and collaboration side risks can be mitigated through supply chain collaboration but supply, finance and environment side risks can be mitigated significantly. Moreover, process and demand side risks cannot be mitigated through collaboration. The theoretical contribution is empirically verifications of the theory of swift, even flow and relational view for all kind of risks.